1
$\begingroup$

Solve the following system of equations ($x,y \in \Bbb R$):

$$\begin{cases} xy-2y-3 &=\sqrt{y-x-1}+\sqrt{y-3x+5} \\ (1-y)\sqrt{2x-y}+2(x-1) &=(2x-y-1)\sqrt{y}. \end{cases}$$

I think this system of equations have no solution, but I can't prove it.

I really appreciate if some one can help me. Thanks!

$\endgroup$
4
  • 2
    $\begingroup$ Maple answers $\{x = 3, y = 5\} $. $\endgroup$ – user64494 Aug 13 '15 at 6:35
  • $\begingroup$ o_0 Yes, you're right. Can you solve it? $\endgroup$ – kimtahe6 Aug 13 '15 at 6:37
  • 3
    $\begingroup$ @ kimtahe6 : What for? What is the aim to solve it? $\endgroup$ – user64494 Aug 13 '15 at 6:57
  • 1
    $\begingroup$ BTW, the solution of the second equation consists of the ray $y=2x-1$ in the first quadrant and the straight line $y=1$. $\endgroup$ – user64494 Aug 13 '15 at 7:07
4
$\begingroup$

Hint: Rewrite the second equation in the form

$(2x-y-1)+(y-1)+(1-y)\sqrt{2x-y}=(2x-y-1)\sqrt y$

Which is equivalent to

$(2x-y-1)(1-\sqrt y)+(1-y)(\sqrt{2x-y}-1)=0$

Or

$(1-\sqrt y)(\sqrt{2x-y}-1)(\sqrt{2x-y}+1+1+\sqrt y)=0$

From here we get $2x-y=1$.

$\endgroup$
2
$\begingroup$

Let me try. One has $y \geq 0$ and $y \leq 2x$.

Then, the second equation can be written as follows:

$$(1-y)\sqrt{2x-y} + (2x-1) -1 - (2x-1)\sqrt{y} + y\sqrt{y} = 0$$

$$(1-\sqrt{y})\left( (1+\sqrt{y})\sqrt{2x-y} + (2x-1) - 1 - \sqrt{y} - y\right) = 0$$

$$(1-\sqrt{y})(\sqrt{y}\sqrt{2x-y}-\sqrt{y} + \sqrt{2x-y} - 1 + (2x-y) -1) = 0$$

$$(1-\sqrt{y})(\sqrt{2x-y}-1)(\sqrt{y}+1+\sqrt{2x-y}+1) = 0$$

Thus, one has $\sqrt{y} = 1$ or $\sqrt{2x-y} = 1$.

The first case: $y = 1$. From this and the first equation, one has

$$x-5 = \sqrt{-x} + \sqrt{6-3x}.$$ But, $x\geq \frac{y}{2} \geq 0$. Then, there is no solution for this case.

The second case: $2x-y = 1$ or $y = 2x-1$. From this and the first equation, one gets:

$$2x^2 - 5x -1 = \sqrt{x-2} + \sqrt{4-x}.$$

$\endgroup$
1
$\begingroup$

To finish, let

$f(x)=2x^2-5x-1\quad \text{and}\quad g(x)=\sqrt{x-2}+\sqrt{4-x}$.

Note that $f(3)=g(3)=2$ and $f(x)$ is increasing $\forall x\in [2,4]$, while $g(x)$ is decreasing when $x\in (3,4]$ and increasing when $x\in [2,3)$.

Thus $x=3$ is the unique solution of $f(x)=g(x)$ in $[2,4]$.

Answer: $x=3, \; y=5$.

$\endgroup$
1
  • 2
    $\begingroup$ Ah thank you for this post. $\endgroup$ – GAVD Aug 13 '15 at 7:42

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.